Directive Speech Actions in the TikTok Comments Column Kompas TV - Desi Andrea; Fatmawati (JURNAL ARBITRER, 2023)
The objective of this study is to investigate and provide a comprehensive analysis of the many roles of directed speech acts seen inside the comment section of @Kompas TV on TikTok. The theoretical framework employed in this study pertains to the analysis of directive speech acts as proposed by Searle. This study employs a qualitative methodology and employs content analysis techniques to facilitate the identification and categorization of data by the researchers. The information was gathered from a TikTok video posted by @Kompas TV that addressed revisions to the Minister of Education’s college admission exams. Included in this research data is every comment made by a netizen that was found to have an intended use. Data collection methods used in this study include note-taking, listening, and documentation. The study’s findings indicated that 848 comments from netizens contained 61 directive expressions. Out of the total of 61 utterances, the set of five functions attributed to directive speech acts comprises the actions of directing, ordering, requesting, advising, and recommending. The most dominant function of directive speech acts is the act of suggesting through 18 utterances. This is due to the intention of the netizen to prompt the recipient of the comment to follow the recommendation expressed. In contrast, the least expression function is advising, which typically involves four data. This is due to the fact that online users frequently offer advice rather than thoughtful criticism that the recipient may or may not find acceptable.